Shelf Life Studies on Potato and Tomato under Evaporative Cooled Storage Structure in Southern Rajasthan - Mishra, B K; Jain, N K; Kumar, Sunil; Doharey, D S; Sharma, K C (Journal of Agricultural Engineering, 2009)
Two most common vegetables viz. potato (var. Kufri Ashoka) and tomato (var. Pusa Ruby) were stored in two tonne capacity evaporative cooling storage structure (ECSS) of CIPHET, Ludhiana design constructed at the Post Harvest Technology Centre, CTAE, Udaipur. Microbial load in form of total viable bacterial count and fungal count were recorded at fortnightly / weekly interval taking in to consideration 10% physiological loss in weight under ECSS as acceptable level. Changes in reducing sugar and soluble protein were also estimated. Total viable bacterial count on potato and tomato were lower in ECSS in comparison to ambient storage. The reducing sugar content and soluble protein content change was slower in ECSS than that at ambient storage in both the stored vegetables. The physiological loss in weight (PLW) was about 6 and 11% less in ECSS compared to ambient for potato and tomato storage, respectively.